The Petroleum Manga: A Project by Marina Zurkow - Zurkow, Marina (punctum books, 2014)
The Petroleum Manga, first conceived of and rendered as 10-foot banners printed on Tyvek for gallery installation is now reproduced in book form. Originally, manga was used in Japanese to refer to whimsical drawings or picture books. Long before manga was a multi-billion-dollar-a-year comic book industry, there was Hokusai's thirteen-volume manga, depicting everything from trees to demons, from squirrels to shingles. This was the work that inspired the form for Marina Zurkow's own crazy amalgam depicting a taxonomy of products derived from petroleum.